Salvia sclarea L. Essential Oil Extract and Its Antioxidative Phytochemical Sclareol Inhibit Oxytocin-Induced Uterine Hypercontraction Dysmenorrhea Model by Inhibiting the Ca2+–MLCK–MLC20 Signaling Cascade: An Ex Vivo and In Vivo Study - Jennifer Wong; Yi-Fen Chiang; Yin-Hwa Shih; Chun-Hui Chiu; Hsin-Yuan Chen; Tzong-Ming Shieh; Kai-Lee Wang; Tsui-Chin Huang; Yong-Han Hong; Shih-Min Hsia (Antioxidants, 2020)
Salvia sclarea essential oil is used as an aromatic therapy for dysmenorrhea. Sclareol—one of the natural products isolated from S. sclarea—displays anti-inflammatory and antioxidant activities; however, researchers have not yet evaluated the mechanism related to the pain-relieving effect of sclareol. In the present study, we aimed to investigate the potential effect of sclareol in ex vivo and in vivo dysmenorrhea models, as well as its possible mechanism. In the ex vivo study of uterine tissue from Sprague Dawley (SD) rats, the uterine contraction amplitude was observed and recorded. In the in vivo study, we measured the uterine contraction pressure of SD rats and performed writhing tests on mice. The uterine tissues from the writhing test subjects were collected and analyzed by Western blot. The results demonstrated that sclareol inhibited prostaglandin (PG) F2α-, oxytocin-, acetylcholine-, carbachol-, KCl-, and Bay K 8644-induced uterine contraction and possessed an analgesic effect in the writhing test. Sclareol affects the Ca2+ level and regulates oxytocin receptor (OTR), myosin light chain kinase (MLCK), extracellular signal-regulated kinase, p-p38, cyclooxygenase-2 (COX-2), and phospho-myosin light chain 20 (p-MLC20) protein expression. Integrating these results, we suggest that sclareol is a potential alternative supplement for dysmenorrhea.